Drivers of Socio-Economic Development Among Ethnic Minority Groups in Vietnam - World Bank (World Bank, Washington, DC, 2019)
While Vietnam has now reached lower middle-income country status, the gaps between the ethnic minority population and the majority group are evident and widening over time. In addition, ethnic minority groups are different in terms of where they are in these gaps. This study attempts to examine why and how certain ethnic groups have managed to rise to the ‘top’ as ‘best performers’ while the other groups seem to stand on the ‘bottom’ as ‘least performers. The key study questions are: (1) What are drivers of the socio-economic development of the different ethnic groups? (2) Why have some ethnic minority groups successfully managed to escape poverty while others have lagged far behind? (3) How have such factors have been addressed in the respective policies and designated programs or projects initiated by the Government of Vietnam, development partners, and other stakeholders? (3) What are the changes needed for future design and implementation of initiatives to support sustainable socio-economic development among ethnic minorities? This study adopts a mixed methodological approach, combining both quantitative and qualitative methods. In order to identify the top- and bottom-performing ethnic minorities, the 2015 Ethnic Minorities Socio-Economic Survey of 53 groups (53EMS) dataset was used to calculate the Human Development Index (HDI) and Multidimensional Poverty Index (MPI) as two indicators of socio-economic development of the ethnic minorities.